Investigation of the Properties of High-Density Polyethylene Pipes used in Kurdistan for Piping System of Potable Water - Hassan, Sarkawt Rostam (Kurdistan Journal of Applied Research, 2022)
High-density polyethylene (HDPE) pipes are recently used in the water distribution network in Kurdistan to replace the old pipes. In this investigation, two types of HDPE pipes (namely A and B) available in the local market have been studied and their properties were compared. Mechanical properties through tensile tests have been investigated and valuable data were collected that could provide a guideline reference for the designers and end-users utilizing these pipes for water supply networks. Furthermore, the HDPE samples were analyzed by differential scanning calorimetry (DSC). Results showed that the ultimate tensile strength recorded for pipe B was greater than pipe A by 8%. Besides, both the elongation at break and strain at break for pipe A was outperformed by almost 6%. On the other hand, the tests showed that the transition from elasticity behavior to ductility behavior for pipe B occurs earlier in comparison to pipe A. It was noted from the gathered information that the two tested pipes were within the standards with variations in their characteristics.